Small creatures with big impacts - International Centre for Insect Physiology and Ecology (Heinrich-Böll-Stiftung, 2022)
Beneficial insects provide enormous ecosystem services to Africa. However, to continue benefitting from these natural processes, sustainable farming and environmental management practices need to be promoted.